A 4-4.8GHz Adaptive Bandwidth, Adaptive Jitter Phase Locked Loop - Taheri, H. E. (Engineering, Technology & Applied Science Research, 2017)
A low power, low phase noise adaptive bandwidth phase locked loop is presented in this paper. The proposed structure benefits from a novel lock status monitor unit (LSMU) that determines loop operation and loop bandwidth. The loop filter resistance and charge pump current are inversely proportional and bandwidth to reference frequency is maintained fixed. This structure is simulated in 0.18 μm CMOS technology and simulation results are presented.